Cash Flow disaggregation and the Prediction of Future Earnings - M. Gh. Osmani; M. H Namdar (مطالعات تجربی حسابداری مالی, 2010)
According to the Iranian Accounting Standard No. 2, alternative use of both direct and indirect methods of reporting cash flows from operating activities is allowed. In practice, despite all persuasive and encouraging measures favoring the direct method, Iranian companies, free in their choice of which method to use, tend to prefer indirect method due to its being easier. Indirect method involves net cash flow reporting rather than a report of each and every element of cash flows from operating activities. This method could be in clear contrast to the general principles concerning the set off between cash inflows and outflows. The general principle dealing with this issue, developed by IASB (2007), declares that setting off cash outflows and inflows is permitted only when presenting the gross numbers is devoid of any informational content. Accordingly, the present study is an effort to examine informational content of Cash ﬂow disaggregation through testing their ability in predicting future earnings of listed companies in Tehran Stock Exchange.  The final goal is to help managers and regulatory authorities with specifying the kind and amount of information to be presented in cash flow statement, and investors with estimating future earnings. Results show that Cash Flow disaggregation, compared to net cash flow from operating activities are better predictors of future earnings.